A Computational Model to Estimate the Performance of 8 inches RO Membranes in Pressure Vessel - Altaee, Ali (Journal of Membrane and Separation Technology, 2012)
A computational model for estimating RO system performance was developed in this study. Wide range of seawater concentrations 32000 mg/L, 35000 mg/L, 38000 mg/L, and 43000 mg/L were used as feed solution. Two different types of Filmtec RO membranes were investigated; SW30HRLE-440i and SW30HR-380. A pressure vessel of four RO elements was simulated in this paper. The recovery rate, ions rejection rate, flow arte, and permeate concentration was simulated for each element in the pressure vessel. The results from this study were compared with Reverse Osmosis System Analysis (ROSA) software assuming that the simulation results from ROSA are reasonably accurate. It was found that the results from this study were in a good agreement with ROSA. The model was also validated against a commercial RO system for seawater desalination, feed concentration 43000 mg/L. An agreement more than 85% was achieved between the model and the experimental data.